Diagnostic ultrasound a logical approach on CD-ROM - McGahan, John P.; Goldberg, Barry B.; Jefferson Medical College (Philadelphia : Lippincott Williams & Wilkins, 2000)
(Producer) A guide to all current applications of ultrasound. It contains the full text and illustrations of the book, plus 30 minutes of narrated video-clips of real-time ultrasound scans and color Doppler ultrasound scans. Coverage encompasses ultrasound of all anatomic regions, as well as obstetric, gynecologic, and pediatric ultrasound, Doppler, endoscopic ultrasound, ultrasound-guided invasive procedures, intraoperative ultrasound, three-dimensional ultrasound, and newer adaptations of ultrasound
Title from disc label
Enhanced CD-ROM version of: Diagnostic ultrasound/ [edited by] John P. McGahan, Barry B. Goldberg. Philadelphia : Lippincott-Raven, c1997
Approved for up to 61.5 hr. of CE credit through Oct. 31, 2000
System requirements: IBM PC or compatible; 8 MB RAM, 11 MB of free hard disk space; Windows 3.1 or higher
System requirements: Macintosh; 8 MB RAM, 8 MB free hard disk space; System 7.1 or higher
Keywords: Ultrasonography -- methods; Ultrasonics -- Diagnostic use; Diagnosis, Ultrasonic